Home for Marine Species: Seagrass Leaves as Vital Spawning Grounds and Food Source - Jiang, Zhijian; Huang, Delian; Fang, Yang; Cui, Lijun; Zhao, Chunyu; Liu, Songlin; Wu, Yunchao; Chen, Qiming; Ranvilage, Chanaka Isuranga Premarathne Maha; He, Jialu; Huang, Xiaoping (Frontiers in Marine Science, 2020)
Seagrass beds provide nursery habitats for marine species. Seagrass leaves, in particular, are used as spawning grounds and food source for fishes and invertebrates, but direct evidence of spawning in seagrass leaves is rare. It is also very challenging to identify eggs through morphological analysis, since the eggs of many marine species appear similar. To accurately identify the eggs on the leaves of the dominant seagrass species in the South China Sea, and evaluate seasonal contribution of seagrass leaves as food source, DNA barcoding and stable isotope technique were conducted. Interestingly, Monetaria annulus was found to spawn on the leaf sheath of Thalassia hemprichii in Li'an gang, Hainan Island. This selection of oviposition site might increase embryo survival compared to the other parts of the seagrass leaves. Meanwhile, the eggs of Stethojulis trilineata were deposited on the entire leaf of Halophila ovalis in Liusha Bay, Guangdong Province. The small fingernail-shaped leaves of H. ovalis might be beneficial for S. trilineata to lay eggs as they are closer to the sediment surface than other seagrass leaves. Based on the stable carbon and nitrogen isotope analyses, the primary food source of M. annulus in summer and in winter were particulate organic matter and seagrass, respectively. The results suggest that seagrass leaf is not only important for fish and invertebrates as a spawning site, but also as a food source. The findings of the present study may support the urgent requirement of the conservation of seagrass beds for sustaining the productivity of marine fisheries.